Community-led comparative genomic and phenotypic analysis of the aquaculture pathogen Pseudomonas baetica a390T sequenced by Ion semiconductor and Nanopore technologies. Issue 9 (22nd March 2018) - Beaton, Ainsley; Lood, Cédric; Cunningham-Oakes, Edward; MacFadyen, Alison; Mullins, Alex J; Bestawy, Walid El; Botelho, João; Chevalier, Sylvie; Coleman, Shannon; Dalzell, Chloe; Dolan, Stephen K; Faccenda, Alberto; et al.
Abstract: Pseudomonas baetica strain a390T is the type strain of this recently described species and here we present its high-contiguity draft genome. To celebrate the 16th International Conference on Pseudomonas, the genome of P. baetica strain a390T was sequenced using a unique combination of Ion Torrent semiconductor and Oxford Nanopore methods as part of a collaborative community-led project. The use of high-quality Ion Torrent sequences with long Nanopore reads gave rapid, high-contiguity and -quality, 16-contig genome sequence. Whole genome phylogenetic analysis places P. baetica within the P. koreensis clade of the P. fluorescens group. Comparison of the main genomic features of P. baetica with a variety of other Pseudomonas spp . suggests that it is a highly adaptable organism, typical of the genus. This strain was originally isolated from the liver of a diseased wedge sole fish, and genotypic and phenotypic analyses show that it is tolerant to osmotic stress and to oxytetracycline. Abstract : Here, we present the high-quality draft genome of Pseudomonas baetica, a bacterial pathogen that has been demonstrated to cause disease in fish cultivated in aquaculture facilities.